Evaluating Course Syllabus: Basis for Reframing into a Learner-Centered Syllabus for Outcome-Based Nursing Education - Albaqawi, Hamdan; Alshammari, Farhan; Pasay-an, Eddieson; Alyami, Mansour; Villareal, Sandro; Dizon, Eliezer (European Scientific Journal, ESJ, 2018)
The shift from customary content-based pedagogical to learnercentered practice is imperative in the 21st century. This research aims to evaluate the course syllabus developed by the faculty members and if the syllabus meets the criteria for the learner-centered syllabus. The study employed a quantitative –comparative design to properly represent the phenomenon. The study was conducted at the selected universities in the Kingdom of Saudi Arabia. Overall, the respondents of the study consist of 100 faculty members and the 50 students from the participating universities in the Kingdom of Saudi Arabia. The researchers adapted the learning-focused syllabus instrument to gather the data. Results show that the faculty members rated the learning goals and objectives to moderate (1.58), while students rated it low (1.42). Likewise, the learning assessment revealed a moderate result (1.76) for faculty members and low (1.38) for the students; the learning activities have moderate (1.69) result for the faculty and low (1.36) for the students. As regards scheduling, faculty members and students reported moderate results having a 2.06 and 2.09 respectively. The classroom environment revealed moderate results both the faculty members (1.62) and the students (1.52). Statistically, there is no significant difference on the category of syllabi when faculty respondents were grouped according to years of teaching (0.699.05). The findings show that the course syllabus evaluated is in a transitional phase towards learner-centered. As such, the progress of the syllabus is potential to meet the criteria for an outcomebased nursing education. However, the varying results as reported suggest reconciliation of the views of the faculty members and the students.